Investigating the evolving microstructure of lithium metal electrodes in 3D using X-ray computed tomography. Issue 33 (10th August 2017) - Taiwo, O. O.; Finegan, D. P.; Paz-Garcia, J. M.; Eastwood, D. S.; Bodey, A. J.; Rau, C.; Hall, S. A.; Brett, D. J. L.; Lee, P. D.; Shearing, P. R.
Abstract : The growth of dendritic and mossy deposits through the separator of lithium batteries can result in battery short circuiting and failure. In situ X-ray CT provides insight into evolution of lithium-metal electrodes during battery operation. Abstract : The growth of electrodeposited lithium microstructures on metallic lithium electrodes has prevented their use in rechargeable lithium batteries due to early performance degradation and safety implications. Understanding the evolution of lithium microstructures during battery operation is crucial for the development of an effective and safe rechargeable lithium-metal battery. This study employs both synchrotron and laboratory X-ray computed tomography to investigate the morphological evolution of the surface of metallic lithium electrodes during a single cell discharge and over numerous cycles, respectively. The formation of surface pits and the growth of mossy lithium deposits through the separator layer are characterised in three-dimensions. This has provided insight into the microstructural evolution of lithium-metal electrodes during rechargeable battery operation, and further understanding of the importance of separator architecture in mitigating lithium dendrite growth.